Associations of adolescent obesity with hypertension, diabetes mellitus and polycystic ovaries in Arabs and Jews in Israel—a nationwide study - Treister-Goltzman, Yulia; Nemet, Dan; Menashe, Idan (Frontiers in Public Health, 2024)
BackgroundPrevious studies on the association of adolescent obesity with comorbid diseases in Israel were conducted predominantly in the Israeli Jewish population.GoalTo compare associations of adolescent obesity with Hypertension (HTN), Diabetes Mellitus type 2 (DM2), and Polycystic ovaries (PCO), singly or in combination, between Arabs and Jews in Israel.MethodsA cross-sectional study of 313,936 Arab adolescents aged 14–19 years between the years 2007–2022, and 289,616 adolescents in a matched Jewish comparison group.ResultsThe crude prevalence of comorbidities increased consistently from the ‘underweight’ to the ‘class 3 obesity’ category (from 0.24 to 6.41%, from 0.32 to 4.59%, and from 0.49 to 5.35% for HTN, DM2 and PCO, respectively). Compared to the reference ‘normal weight’ category, an incremental increase of aOR was observed by increasing weight category. The aORs for the ‘class 3 obesity’ category (95% CIs) were 26.00 (21.62–31.10), 10.82 (8.83–13.14), and 6.06 (95% CI 4.57–7.87) for HTN, DM2, and PCO, respectively. In the Jewish comparison group, lower aORs for HTN and DM2 were observed in the ‘class 3 obesity’ category. The increase in aORs with the increase in weight categories was more striking in cases of multiple comorbidities.ConclusionThe finding of a strong association of obesity severity with major cardiometabolic consequences in adolescence, as well as the unique ethnic features of these associations, can help focus national health initiatives on vulnerable adolescent groups.